Advances in the Surgical Management of Ankle Fractures. Issue 4 (11th November 2019) - Wright, David J.; Bariteau, Jason T.; Hsu, Andrew R.
Ankle fractures are one of the most common injuries treated by orthopedic surgeons worldwide. However, operative indications, techniques, and reported outcomes following operative fixation vary widely in the literature. This evidence-based review focuses on recent advances in the operative management of ankle fractures including arthroscopic-assisted surgery, deltoid ligament complex repair, expanded indications for posterior malleolus fixation, fibula intramedullary nailing, and dynamic syndesmosis repair. Level of Evidence: Level V, expert opinion.